Effect of the ethanol extract of Pereskia bleo (Kunth) DC. on the blood pressure and electrolyte levels of hypertensive rats - Siska Siska; Endang Hanani; Tahyatul Bariroh; Benny Febrianto; Anggraita Dewi Amalia Putri Pratiwi; Nadhif Naufala Yaner; Nur Alfaeni Fitri (Shahrekord University of Medical Sciences, 2023)
Introduction: The green cactus Pereskia bleo is thought to have anti-cancer, anti-tumor, anti-inflammatory, and anti-rheumatic properties. Additionally, it treats hypertension and diabetes; However, no scientific evaluation of its antihypertensive activity has been conducted. The purpose of this study was to investigate the effects of oral administration of P. bleo extract (PBE) on male rats' blood pressure, urine volume, and sodium and potassium levels. Methods: Sodium chloride (NaCl) solution (4%) was administered orally to induce hypertension. A non-invasive tail method was used to measure blood pressure. The sodium and potassium concentrations as well as the total volume of urine were measured from the collected urine. Results: Hypertensive rats' blood pressure was reduced by 250, 500, and 1000 mg/kg of PBE. Similar to the positive control group (captopril dose of 1.25 mg/kg BW), the most significant drop in blood pressure was occurred at the dose of 1000 mg/kg BW (P>0.05). All treatment groups saw an increase in urinary sodium and potassium levels. Conclusion: In NaCl-induced hypertensive rats, oral administration of P. bleo ethanolic extract decreased blood pressure to the standard value by increasing urinary sodium and potassium levels. Hence, it might be used as an anti-hypertensive agent.